Geosynthetic tubes and mats : experimental and analytical studies - Guo, Wei (2012)
Geosynthetic tube has been widely used in projects for coastal protection, dike construction, flood control and dewatering waste sludge in many countries. In order to improve our understanding of the performances of geosynthetic tubes or mats and develop reliable design tools, both experimental and analytical/numerical studies were carried out. Closed-form solutions for the design of water or slurry inflated impermeable geosynthetic tubes resting on rigid foundation were derived. With these solutions, the tensile force along the tube, the contact width with ground, the width, height, perimeter, and area of cross-section of a geosynthetic tube could easily be calculated even without considering the whole cross-section. Relatively large scale model tests using geosynthetic tubes of up to 4 m long and 2 m wide were carried out. The results of the closed-form solutions agreed well with the model test results. A so-called e-log p method was proposed for the analysis of geosynthetic tubes or mats on deformable foundation. This method was evaluated against numerical results using FLAC and compared with the existing method using Winkler foundation. The comparisons showed that the proposed e-log p method agreed better with the numerical results particularly when geosynthetic mat was analyzed. A new reinforced seaming method was developed to improve the seam efficiency of relatively weak geosynthetic sheets with seams. This so-called “RJ” method increased the seam efficiency from the normal 50% to over 75%. Theoretical methods for analyzing the cross-section and tensile forces at the end of filling and for calculating the deformation of the geosynthetic tubes during the dewatering process were proposed. The results of the theoretical methods agreed well with the model test results. To accelerate the dewatering process of waste sludge using permeable geosynthetic tubes, the existing stacking method was evaluated using model tests. A new method, the so-called vacuum method, was proposed to improve the dewater efficiency. The model test results showed that the vacuum method could not only accelerate the dewatering process, but also reduce the tensile strength of the geotextile used for the tube.